2021
DOI: 10.1007/s00125-021-05596-z
|View full text |Cite
|
Sign up to set email alerts
|

Dietary palmitate and oleate differently modulate insulin sensitivity in human skeletal muscle

Abstract: Aims/hypothesis Energy-dense nutrition generally induces insulin resistance, but dietary composition may differently affect glucose metabolism. This study investigated initial effects of monounsaturated vs saturated lipid meals on basal and insulin-stimulated myocellular glucose metabolism and insulin signalling. Methods In a randomised crossover study, 16 lean metabolically healthy volunteers received single meals containing safflower oil (SAF), palm oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Human studies have revealed that the acute consumption of saturated fatty acid [ 135 ] and monounsaturated fatty acid [ 136 ] results in systemic, hepatic, and adipose tissue insulin resistance during the postprandial phase in healthy volunteers. A similar rapid induction of insulin resistance has been observed in skeletal muscle, although saturated fatty acids induced higher levels of ceramides and activated different protein kinase C isoforms compared to monounsaturated fatty acids, a possible explanation for discrepancies in long-term outcomes [ 137 ]. It is hypothesized that repetitive nutrient overload is the impetus for cardiometabolic pathogenesis.…”
Section: How Phenotype Flexibility Is Lostmentioning
confidence: 84%
“…Human studies have revealed that the acute consumption of saturated fatty acid [ 135 ] and monounsaturated fatty acid [ 136 ] results in systemic, hepatic, and adipose tissue insulin resistance during the postprandial phase in healthy volunteers. A similar rapid induction of insulin resistance has been observed in skeletal muscle, although saturated fatty acids induced higher levels of ceramides and activated different protein kinase C isoforms compared to monounsaturated fatty acids, a possible explanation for discrepancies in long-term outcomes [ 137 ]. It is hypothesized that repetitive nutrient overload is the impetus for cardiometabolic pathogenesis.…”
Section: How Phenotype Flexibility Is Lostmentioning
confidence: 84%
“…e disruption of carbohydrate metabolism, highlighted by many authors [28][29][30][31][32][33], was marked by muscle insulin resistance induced by significant decrease in Akt activation [34,35], which promoted the increase in insulin levels [36] and HOMA-IR with all HFD. Otherwise, it has been observed that high OO diet over a long period of time induces obesity and insulin resistance similar to what is observed with lard-based diet [37].…”
Section: Discussionmentioning
confidence: 99%
“…Recent data suggest that not only total SkM fat content but also lipid composition [ 63 ] is important for IR. A recent study showed that oleate may activate the SkM sn1,2-DAG–PKC theta pathway to induce IR and that palmitate favors ceramide accumulation and PKC zeta–PP2A activation, which may aggravate SkM IR [ 64 ]. The effects of PA on these conditions remain unknown.…”
Section: Effects Of Long-term Pa On Irmentioning
confidence: 99%